The Effect of Formative Assessment Practices on English Learning Achievement among Senior High School Students: A Quantitative Study - Ashifa Qolbi; Fitria Farizza; Putri Alia Azzahwa; Yunita Sari Adelina (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study examined the effect of formative assessment practices on English learning achievement among senior high school students. A quantitative correlational design was employed involving 312 Grade XI students selected through stratified random sampling from six senior high schools. Data were collected using a 28-item Formative Assessment Questionnaire (Cronbach's Alpha = 0.931) and a 50-item English Achievement Test (KR-20 = 0.903). The instruments demonstrated satisfactory validity, with factor loadings ranging from 0.648 to 0.882. Descriptive analysis indicated that the mean score for formative assessment practices was 3.86 (SD = 0.54), while students' mean English achievement score was 78.42 (SD = 8.61). Pearson correlation analysis revealed a significant positive relationship between formative assessment practices and English achievement (r = 0.684, p < .001). Regression analysis showed that formative assessment significantly predicted English achievement (β = 0.671, p < .001), explaining 46.8% of the variance (R² = 0.468). These findings indicate that effective formative assessment significantly improves students' English learning outcomes in senior high schools.